On the filtered Smith predictor with feedforward compensation. (May 2016) - Rodríguez, C.; Normey-Rico, J.E.; Guzmán, J.L.; Berenguel, M.
Abstract : Highlights: We propose a general structure for dead-time and measurable disturbance compensation. Simple tuning rules for typical industrial models are proposed. Discrete implementation of the controller is discussed to ensure internal stability. Performance benefits are shown in simulation including three industrial processes. Abstract: This paper discusses about a general implementation structure of the filtered Smith predictor for single-input single-output processes with a measurable disturbance. Dead-time free models are used to feed-forward the measurable disturbance into the feedback controller. It is demonstrated that the proposed controller can be applied to control open-loop unstable processes with different time delays associated with control and disturbance signals. Different simulated industrial processes are used to illustrate the proposed strategy properties and advantages over other time-delay compensators.